Transforming English Language Education: The Role of Filipino Assistant Language Teachers in Japan's Internationalization Efforts - Pontawe Casingal, Cyrus; Rivero Caerlang, Lovejoy (International Journal of Educational Review, 2025)
This study examines the experiences, challenges, and contributions of Filipino Assistant Language Teachers (ALTs) in Japan's educational system. Employing a mixed methods approach, data were collected from seven Filipino ALTs across different Japanese prefectures through structured questionnaires examining demographic characteristics and professional experiences, complemented by in-depth narrative accounts of their cultural adaptation processes. Findings reveal that Filipino ALTs navigate complex cultural territories in their professional practice. In doing so, they develop hybridized professional identities that bridge Filipino and Japanese educational paradigms. These educators integrate distinctive pedagogical approaches from Philippine educational practices, including interactive learning strategies and culturally responsive teaching methods. Language barriers emerged as the most significant challenge. However, participants demonstrated remarkable resilience in developing adaptation strategies to overcome these obstacles.The unique cultural positioning of Filipino ALTs as Asian English language educators challenges traditional assumptions about native speaker models. Their experiences offer innovative approaches to cross-cultural education that draw from both Eastern pedagogical traditions. This research contributes to understanding how teachers from diverse cultural backgrounds navigate international educational contexts. It demonstrates how these educators develop professional identities that bridge multiple cultural traditions while maintaining their distinctive pedagogical contributions.